Comparative Risk Assessment Study of Elemental Impurities in Montelukast Chewable Tablets and Film-coated Tablets - Angelevski, Stefan; Slaveska Spirevska, Irena; Lazarevska Todevska, Elena; Bakovska Stoimenova, Tanja; Glavaš Dodov, Marija; Simonoska Crcarevska, Maja; Slaveska Raički, Renata (Archives of Pharmacy, 2023)
It is well documented that elemental impurities (EIs) are critical in the field of pharmaceutical development since they could affect the quality, efficacy and safety of the finished dosage form (FDF). The responsibility of pharmaceutical manufacturers is to demonstrate via assessment approach, risk-based control strategy and/or required data analysis that the FDFs are compliant with ICH Q3D (R2). The aim of this research is to conduct a comprehensive comparative EIs risk assessment study of three different Montelukast dosage forms produced as chewable tablets (4 mg and 5 mg) and film-coated tablets 10 mg. The inductively coupled plasma-mass spectrometry (ICP-MS) system was used for the determination of EIs in samples of Montelukast sodium as the active pharmaceutical ingredient (API), placebos for all FDFs, and FDFs. Moreover, the analyses were also conducted on three batches from all three studied FDFs. Based on ICH Q3D (R2) guidelines, the tested products for EIs Class 1 and Class 2A showed that EIs levels in the API and placebos are well below the ICH Option 1 oral and parenteral limits. For the examined batches of each FDF strength (total of 9), none of the EI exceeds their concentration limits.
Keywords: elemental impurities; Montelukast; risk assessment; ICH Q3D (R2); comparative study